Best Answer

2*sqrt(3)*sqrt(12) = 2*sqrt(3)*sqrt(4*3)

= 2*sqrt(3)*sqrt(4)*sqrt(3)

= 2*sqrt(3)*2*sqrt(3)

= 4*sqrt(3)*sqrt(3) = 4*3 = 12

Q: What is 2 square root of 3 square root of 12?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2 root 3 over 2, so square root of 3

To simplify the square root of 12: Look at numbers that can be reduced from the larger number and can be square rooted itself. 4 * 3 = 12 The square root of 4 is 2. Therefore the simplification of the square root of 12 is: 2*square root of 3

2 Square(3)

It works out as -26 times the square root of 3

To multiply 2 square root of 2 by 3 square root of 6, simplify each square root separately first: 2 square root of 2 simplifies to 2√2, and 3 square root of 6 simplifies to 3√6. Then, multiply the coefficients (2 and 3) to get 6, and multiply the square roots (√2 and √6) to get √(2x6) = √12. So, the final answer is 6√12.

Related questions

The square root of 12 equals the square root of 4 times 3. The square root of 4 is 2. The square root of 12 equals 2 times the square root of 3.

hmm... okay, if I understand you correctly, 2 times the square root of 3 times the square root of 12? = 2(1.73)(3.46) = 11.9716. If you aren't using the approximations, then just simplifying is... [sorry, I can't do the square root sign on the computer...] 2(square root of 3)(square root of 12) = 2(square root of 3)(square root of 4*3) = 4(square root of 3)(square root of 3) = 4(3) = 12!!! HOPE I HELPED!! :-)

2 root 3 over 2, so square root of 3

To simplify the square root of 12: Look at numbers that can be reduced from the larger number and can be square rooted itself. 4 * 3 = 12 The square root of 4 is 2. Therefore the simplification of the square root of 12 is: 2*square root of 3

2 Square(3)

It works out as -26 times the square root of 3

To multiply 2 square root of 2 by 3 square root of 6, simplify each square root separately first: 2 square root of 2 simplifies to 2√2, and 3 square root of 6 simplifies to 3√6. Then, multiply the coefficients (2 and 3) to get 6, and multiply the square roots (√2 and √6) to get √(2x6) = √12. So, the final answer is 6√12.

√12 = √4 × √3 = 2√3 √18 = √2 × √9 = 3√2 √12 × √18 = 6√2√3 √12 × √18 ≈ 14.7

square root of 12 = sq rt of (4 x3) = 2 x sq rt 3

2√3

√12 = 2√3 √8 = 2√2

It doesn't factor neatly. If you solve it, you get the square root of 12/7 which is either 2 times the square root of 3/7 or -2 times the square root of 3/7